A Randomised, Double-Blind Pilot Study of Enzyme-Potentiated Desensitisation for Prophylaxis of Large Local Reactions to Mosquito Bites. (22nd March 2012) - Berkovitz, S.; Hill, N.; Radcliffe, M.; Ambler, G.
Abstract : Primary Objective . To test the hypothesis that two injections of enzyme-potentiated mosquito antigen significantly reduce the size of experimental mosquito bites in participants with LLR-MB. Design . Randomised, double-blind, placebo-controlled, parallel group comparison over 3 months. Setting . Hospital outpatient clinic. Participants . Fifty adult participants of both sexes. Interventions . Two injections of mosquito antigen or matching placebo, 6 weeks apart. Main Outcome Measures . Early (1 hour) and late (24 hours) mean square root of erythema area (SREA) following controlled mosquito bite with the second bite given at least 6 weeks following the final injection. Results . At 1 hour, mean SREA was slightly higher in the EPD group compared to placebo after adjusting for baseline values (0.46, 95% CI − 6 .11 to 7.03), but this was not statistically significant (P = 0.89, ANCOVA analysis); neither were the results at 24 hours (− 2 .58, 95% CI − 11 .73 to 6.57) (P = 0.57 ). The proportion of participants experiencing a decrease in wheal size at 1 or 24 hours was similar between groups. Conclusions . EPD was not demonstrated to be effective for immediate or delayed LLR-MB. Methodological problems included a high variability in LLR-MB between subjects, suggesting that a crossover design should be used in future.